The role of emotional mediation in visitor experiences in art tourism: based on stimulus-organism-response model - Hao, Yingyi; Hasna, Mohd Fabian; Abdul Aziz, Faziawati (Springer, 2024)
Despite the growing body of research on the impact of art on emotions and psychology, there is limited exploration of the role of emotional factors in visitor experiences in art spaces. Therefore, this study focuses on the Stimulus-organism-response (SOR) model to investigate the relationship between visual stimuli and tourist satisfaction in art venues. The main objective is to gain a deeper understanding of the mechanisms of the emotions and responses of art tourists and to provide practical strategies and recommendations for planning and managing public art spaces. By obtaining data from 603 valid samples supported by field surveys and sample surveys, this study used structural equation modeling and multiple regression analysis to test the theoretical framework while analyzing the data in depth. The results show that the aesthetic experience mediates visual quality and tourists’ satisfaction, and cultural identity can moderate the relationship between visual quality and aesthetic experience. These findings will help managers better understand the importance of aesthetic experience in tourists’ responses and make a significant theoretical contribution and practical importance to enhancing tourist satisfaction in art tourism destinations.